Effect of berries and fruits on cognitive change during a 2‐year multi‐domain lifestyle intervention: The Finnish Geriatric Intervention Study to Prevent Cognitive Impairment and Disability (FINGER): Prevention (nonpharmacological) / Nutrition. (7th December 2020) - Eskelinen, Marjo H; Solomon, Alina; Ngandu, Tiia; Antikainen, Riitta; Hänninen, Tuomo; Laatikainen, Tiina; Lindstrom, Jaana; Paajanen, Teemu; Soininen, Hilkka; Strandberg, Timo; Tuomilehto, Jaakko; Kivipelto, Miia; et al.
Abstract: Background: Dietary components such as berries and fruits are part of the recommended Nordic diet, and are considered having health‐enhancing characteristics. A randomized multi‐center and multi‐domain lifestyle intervention trial FINGER has shown benefits on cognition with dietary guidance, exercise, cognitive training and vascular risk management. Here, we investigate the association between berry and fruit intake at baseline and cognitive function over 2 years. Methods: Individuals aged 60‐77 years were randomly assigned in a 1:1 ratio to intervention (n=631, nutritional guidance, exercise, cognitive training, and management of metabolic and vascular risk factors) or control group (n=629, general health advice). A modified neuropsychological test battery and 3‐day food records were administered annually. Mixed‐model repeated‐measures analyses with maximum likelihood estimation were used to analyse change in cognitive scores as a function of randomization group, time, berry consumption, total energy intake, berry consumption x time interaction, group x time interaction, energy intake x time interaction, age x time interaction, age, sex, education, study site, C‐reactive protein, systolic blood pressure, and low‐density lipoprotein cholesterol. A similar model was used to investigate effects of fruit consumption. Results: High berry consumption at baseline compared with no berry consumption was associated with more improvement in all investigated cognitive domains. Berry consumption x time interaction coefficient (95% CI) was for global cognition 0.058 (0.034‐0.082), p<0.001; for executive functioning 0.050 (0.018‐0.081), p=0.002; for memory 0.069 (0.028‐0.109), p=0.001; and for processing speed 0.051 (0.018‐0.085), p=0.003 over two years. When berry consumption was combined with fruit consumption, the results remained similar. However, fruit consumption alone did not show any association with the cognitive domains. Conclusions: Berries are an important component of the Nordic diet, and higher consumption of berries seems to have a beneficial impact on cognitive functioning. Several healthy components such as flavonoids in berries might be behind this association, e.g. by influencing cerebrovascular blood flow and synaptic plasticity of the brain. Acknowledgements: The presenting author wish to acknowledge The Juho Vainio Foundation; Yrjö Jahnsson Foundation; Päivikki and Sakari Sohlberg Foundation.